Left colic artery–preserving radical rectal cancer surgery: a literature review - Yang, Xiyin; Sun, Yuanshui; Hu, Qiang (Frontiers in Surgery, 2026)
ObjectiveTo review current evidence on left colic artery (LCA) preservation during radical rectal-cancer surgery, covering anatomic rationale, surgical techniques, oncologic safety and functional outcomes.MethodsPubMed, Embase, the Cochrane Library and CNKI were comprehensively searched for randomized trials, cohort studies and meta-analyses published in the past two decades that compared high-tie inferior mesenteric artery (IMA) ligation with low-tie LCA-preserving procedures. Key end-points included overall survival (OS), disease-free survival (DFS), local recurrence, anastomotic leak, urogenital and bowel function, and peri-operative recovery.ResultsAcross the aggregated literature, five-year OS, DFS, local-recurrence rates and R0 resection rates did not differ significantly between the two ligation strategies. Preserving the LCA consistently reduced clinical anastomotic leaks and was associated with better postoperative urinary, sexual and bowel function, as well as marginally shorter hospital stay and time to gastrointestinal recovery. Pre-operative CTA or MRA accurately delineates IMA-LCA branching patterns and collateral integrity, while intra-operative indocyanine-green fluorescence provides real-time perfusion assessment; emerging artificial-intelligence models show promise in refining both pre-operative planning and intra-operative decision-making.ConclusionsWhen meticulous D3 lymph-node clearance is maintained, LCA preservation delivers oncologic outcomes equivalent to high-tie ligation while offering notable advantages in peri-operative safety and long-term function. Consequently, low-tie LCA-preserving resection should be considered the preferred approach for most low-anterior resections unless specific anatomic or oncologic contraindications exist. Future multicentre randomised trials and AI-assisted studies are warranted to identify high-risk subgroups and optimise patient-specific indications.